Prototype Aplikasi Informasi Wisata Kabupaten Lebong Berbasis Android - pebriano, pigo; Abdullah, Dedy; Khairullah; Hidayah, Agung Kharisma (Institut Informatika Dan Bisnis Darmajaya, 2025)
This research is motivated by the lack of a structured and easily accessible tourism information system in Lebong Regency, despite its significant potential in natural, cultural, and historical tourism. The aim of this study is to design and develop a prototype of a tourism information application based on Android that presents destination data in a structured and interactive manner. The methodology used is the Prototype method, consisting of communication, quick design, construction, and testing stages. The application was developed using the Kodular platform and supported by Firebase and Google Spreadsheet for data storage. The application provides information about tourist attractions, hotels, culinary spots, gas stations, local history, and location routes. The results indicate that the application successfully presents comprehensive and accurate tourism information and offers a positive user experience based on Black Box testing and user questionnaires. In conclusion, this application serves as an effective digital medium for supporting tourism promotion and assisting tourists in planning their visits to Lebong Regency.